Response Of Giving Antagonist Fungi Trichodema Spp On Vegetative Growth Of Soybean Plants (Glycine max (L) Merr.) Infected By Fusarium Sp. - Maftukhah, Nur Aini; Faizah, Mazidatul (AGARICUS: Advances Agriculture Science & Farming, 2023)
Biological control is the use of antagonistic agents to control plant pathogens. One of the biological agents currently being developed is Trichoderma spp. Trichoderma spp fungi are often used to control Fusarium sp (root wilt disease). Trichoderma spp fungi have the ability to increase the growth rate and development of plants, especially their ability to cause healthy root production and increase root depth (deeper in the soil surface). Therefore, the author aims to examine the response of Trichoderma spp antagonistic fungi to the vegetative growth of soybean plants (Glycine max (L) Merr.) Infected with Fusarium sp. This study was conducted using an experimental method using a single factor Completely Randomized Design (CRD) consisting of T0F0, T0F10, T10F10, T15F10. Each consists of 4 replications. The results of the study showed that Trichoderma spp played a significant role in the process of inhibiting the growth of Fusarium sp in root development, plant height, development of the number of leaves and functioned to provide nutrients for plants causing plant cell metabolism to run better so that plant growth during the vegetative phase did not experience obstacles. Keywords: soybean plants (Glycine max (L) merr.), Fusarium sp (root wilt disease), Trichoderma spp